2010
DOI: 10.1089/ten.tea.2009.0518
|View full text |Cite
|
Sign up to set email alerts
|

Stem/Progenitor Cell–Mediated De Novo Regeneration of Dental Pulp with Newly Deposited Continuous Layer of Dentin in an In Vivo Model

Abstract: The ultimate goal of this study is to regenerate lost dental pulp and dentin via stem/progenitor cell-based approaches and tissue engineering technologies. In this study, we tested the possibility of regenerating vascularized human dental pulp in emptied root canal space and producing new dentin on existing dentinal walls using a stem/progenitor cell-mediated approach with a human root fragment and an immunocompromised mouse model. Stem/progenitor cells from apical papilla and dental pulp stem cells were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
494
1
18

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(531 citation statements)
references
References 27 publications
18
494
1
18
Order By: Relevance
“…Two exceptions to this are the ability of pericytes to regenerate chemoablated Leydig cells in the rat testis 69 and white adipocyte progenitors belonging to the mural cell compartment in mouse adipose tissue vasculature. 56 These observations must be confirmed within multiple other cell lineages before a generalized role of perivascular cells in tissue homeostasis can be concluded. Nevertheless, as previously illustrated, perivascular cells are strong candidates for medical tissue regeneration, even before expansion in culture into MSC-like 72 and are, therefore, candidate trophic "drugstore" cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Two exceptions to this are the ability of pericytes to regenerate chemoablated Leydig cells in the rat testis 69 and white adipocyte progenitors belonging to the mural cell compartment in mouse adipose tissue vasculature. 56 These observations must be confirmed within multiple other cell lineages before a generalized role of perivascular cells in tissue homeostasis can be concluded. Nevertheless, as previously illustrated, perivascular cells are strong candidates for medical tissue regeneration, even before expansion in culture into MSC-like 72 and are, therefore, candidate trophic "drugstore" cells.…”
Section: Resultsmentioning
confidence: 98%
“…9,15,[55][56][57] These discoveries imply that pericytes can potentially be applied to bone regeneration, dental repair, and adipose reconstruction.…”
Section: Pericytes: Applications In Tissue Repair and Regenerationmentioning
confidence: 99%
“…In the presence of a fibrin gel, structured tissues similar to normal pulp were observed after 12 weeks of implantation. Previous studies demonstrated either adipose tissues or ectopic mineral deposition in the canal space of whole teeth or tooth fragments implanted in rodents (9,21). A recent study in immature, formerly infected teeth in dogs, suggested that an injectable scaffold is unnecessary for pulp regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth like structures have been obtained by seeding dental pulp stem cells on PLGA scaffolds. [62] Bioactive ceramics:-Calcium phosphate ceramics such as hydroxyapatite (HA), betatricalcium phosphate (β-TCP), and biphasic calcium phosphate (BCP) are totally biocompatible and bioactive crystallized materials. [63,64] Cells cultured on the porous form of ceramics could attach, proliferate, and expressed dentin sialophosphoprotein, which is a dentin marker.…”
Section: Issn: 2320-5407mentioning
confidence: 99%